A comparative study of x-ray shielding capability in ion-implanted acrylic and glass - Noor Azman, N.; Siddiqui, Salim; Ionescu, M.; Low, It Meng (Pergamon, 2013)
Samples of acrylic and glass were implanted with tungsten (W) and lead (Pb) to investigate their X-ray attenuation characteristics. The near-surface composition depth profiles of ion-implanted acrylic and glass samples were studied using ion-beam analysis (Rutherford backscattering spectroscopy—RBS). The effect of implanted ions on the X-ray attenuation ability was studied using a conventional laboratory X-ray machine with X-ray tube voltages ranging from 40 to 100 kV at constant exposure 10 mAs. The results were compared with previous work on ion-implanted epoxy. As predicted, the RBS results and X-ray attenuation for both ion-implanted acrylic and glass increase with the type of implanted ions when compared to the controls. However, since the glass is denser than epoxy or acrylic, it has provided the higher X-ray attenuation property and higher RBS ion concentration implanted with a shorter range of the ion depth profile when compared to epoxy and acrylic. A prolonged time is necessary for implanting acrylic with a very high nominal dose to minimize a high possibility of acrylic to melt during the process.